Flexibel newspapers holder - Shari, Sharunizam; Mamat Nawi, Azmir; Ahmad Zamri, Ahmad Fazlan (Universiti Teknologi MARA, Kedah, 2017)
The large size of newspapers cause problems to the library. The traditional method of displaying newspapers is to place them on newspapers rack with the newspapers being bound by wooden sticks as a holder. The proposed design enhanced the looks and functions of the wooden sticks. Flexible newspapers holder is much more compact and sleek than the traditional wooden sticks. Apart from fasten the newspapers, the flexible newspapers holder can also serve as a frame to hold the newspapers for displaying purpose.